Carboxymethyl Starch (CMS) from Taro (Colocasia esculenta L.) as a Binder in Paracetamol Tablet - Syamsidi, Armini; Musili, Silvana; Sultan, Asriana; Yusriadi, Yusriadi (Fakultas Farmasi, Universitas Surabaya, 2026)
Taro tubers (Colocasia esculenta L.) are a potential source of starch for use as a tablet binder. However, the limited flowability of native starch necessitates chemical modification to ensure consistent binder performance in tablet formulation. This study evaluated carboxymethyl starch (CMS) derived from taro tubers in comparison with native starch and investigated the effect of CMS concentration on the quality of paracetamol tablet formulation. CMS was synthesized from taro starch, characterized for flowability parameters and angle of repose, then applied as a binder at concentrations of 3% (F1), 5% (F2), 10% (F3), and 15% (F4), with native starch 5% (F0) and HPMC 5% (F5) used as a control. Tablet quality was evaluated in terms of weight uniformity, friability, hardness, disintegration time, and dissolution. CMS exhibited improved flow properties compared to native starch, with a Carr’s index of 16.43% and a flow rate at 1.19 g/s, indicating fairly good flowability. Tablets formulated with CMS demonstrated acceptable physicochemical characteristics, particularly at concentrations 5-10% (F2 and F3), which met pharmacopeial requirements for friability (<1%), hardness (4-8 kg), and disintegration time (<15 min), then showed comparable performance to HPMC. In conclusion, taro-based CMS is a promising natural binder that enhances tablet mechanical strength and reduces friability in paracetamol tablet formulations.